Potentiality of graphene as a base material for impact ionization avalanche transit time diode in high-frequency applications - Swain, Mamata Rani; Tripathy, Pravash Ranjan (Bulletin of Electrical Engineering and Informatics, 2024)
In this paper, the microwave application potential of graphene is studied using a double-drift-region (DDR) impact ionization avalanche transit time (IMPATT) diode. The simulation of this diode is carried out for the very first time at several different atmospheric window frequencies. Because graphene has unique and special properties, it could be used to make electronic gadgets for the next generation. The device is simulated at a variety of millimeter and sub-millimeter wave frequencies using a model called self-consistent drift diffusion (SCDD), which was developed by the author based on current continuity, Poisson’s equation and space charge equation. When compared to traditional IMPATT devices such as Si, GaAs, InP and GaP, the results demonstrate superior performance in terms of efficiency, and RF power across a wide range of operating conditions. Again, the behavior of noise in graphene IMPATT is studied, and it is found that it makes less noise than Si and GaAs IMPATT. The simulation results open up new avenues for IMPATT diode manufacture and design.